Looking through the Ethnolinguistic Perspective to Unveil the Social Facts Phenomenon of Piil Pesenggiri - Ninsiana, Widhya (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
This article discusses the issues around the socio-cultural phenomenon that employ interdisciplinary studies between linguistics, anthropology and sociology to study the linguistic behaviors of the Lampungese society in a way to grasp their worldview. The data were technically collected through observation and literature reviews to bring out the voices and experiences of the people who mostly affected by the concept of Piil Pesenggiri, of people whose voices have been missing in literature and debate. The production and reproduction of identity through Piil Pesenggiri seems to remain a finding tradition exist among the Lampungese which primarily resulted both demographic and the local political change allowing emergence of a capitalist strategy "retreatment" used as a form of resistance against the transmigrants. It is not a secret anymore that Piil Pesenggiri which many of us understood as the life philosophy of Lampungese triggers negative stigma amongst other shared races or tribes of transmigrants, it is a shift of viewing piil as a mere "cultural shield" or cultural fortress within their social relations. It then becomes clear that the worldview of the social facts of the community as well as segregation that plunges into the socio-political aspects of society including education, cultural symbols, the political flow of identification of social structures. Todays, the existence of Piil Pesenggiri ethnolinguistically is deemed to reflect cultural capital, a static and contextual product of identity which cannot be separated from the people (ulun) Lampung. The empirical information obtained by this research is expected to be utilized by various stakeholders concerning the problem of relations between ethnic groups in taking the attitude, policy and purposes of a scholarship. Such studies are of course useful not only for reconciliation to conflicts involving the ethnic communities, but also to the ability to maintain a well-created social harmony as well.